Establishing judicial accountability in the Iraqi environment and its role in reducing administrative and financial corruption (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the role of forensic accounting in reducing administrative and financial corruption in the Iraqi environment and its impact on society, and to demonstrate the correlation between forensic accounting and administrative and financial corruption. A sample of insurance companies operating in Iraq was selected as a research community. To achieve this research and prove its hypotheses, a questionnaire was distributed according to the research variables using statistical methods. The relationship between the variables was analyzed: the independent variable (forensic accounting) and the dependent variable (financial and administrative corruption). The research concluded that the results of the statistical analysis of the correlation relationships between the independent variable (forensic accounting) and the dependent variable (administrative and financial corruption) reached a correlation value of (0.76), which is a positive significant value at a significance level of (0.01). According to the decision rule used, the hypothesis was accepted, and the correlation value indicates that the independent variable has a good ability to predict the dependent variable, because the value is close to one. The closer the value is to one, the better the independent variable becomes in predicting the dependent variable (administrative and financial corruption). The research also concluded that corrupt financial and administrative practices can be reduced by integrating forensic accounting methods and procedures, as these methods enhance financial information and provide reliable accounting and legal techniques to detect violations. The research recommends the need to rely on forensic accounting services in the Iraqi environment to help achieve fair results by examining financial records and reducing administrative and financial corruption. The need to introduce forensic accounting into the curricula of the accounting subject in postgraduate studies to increase students' knowledge of the concept of forensic accounting, as well as increase researchers in forensic accounting and their familiarity with its requirements, with the establishment of an official accreditation mechanism in judicial disputes to coordinate between Iraqi universities and the Iraqi Judicial Council.